Bent [videorecording (DVD)] - Moresco, Robert; Urban, Karl, 1972-; Vergara, Sofía, 1972-; Garcia, Andy; Byers, Grace, 1984-; Spano, Vincent, 1962-; Finn, John, 1952-; Cornelisse, Tonya; Sanz, Elena (Lions Gate Entertainment, 2018)
When a drug bust goes wrong, ex-cop Danny Gallagher's quest for justice leads him to the car-bomb murder of a government official's wife. When Gallagher learns that the woman's secret lover was a seductive federal agent, he finds himself under fire. But from whom, his own cops, a vengeful drug lord, the CIA, or someone even more ruthless?